1998
DOI: 10.1093/bja/80.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Propofol and intralipid interact with reactive oxygen species: a chemiluminescence study

Abstract: We have studied the ability of propofol and Intralipid to inhibit reactive oxygen species generated either by stimulated human leucocytes or cell-free systems using luminol chemiluminescence. Human leucocytes were stimulated by a chemotactic peptide, FMLP 1 mumol litre-1, or by a phorbol ester, PMA (protein kinase C activator) 0.1 mumol litre-1. In cell-free experiments, superoxide-hydrogen peroxide, hypochlorous acid or hydroxyl radical-induced chemiluminescence responses were initiated by xanthine 0.1 mmol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…In a human leukocyte chemiluminescence study, Demiryurek et al reported that PPF possesses a direct scavenging effect on hydroxyl chloride, superoxide, hydrogen peroxide and hydroxyl radical. 10 Our data suggest that PPF has no such effects on the direct scavenging of nitric oxide. Therefore, the protective mechanism of PPF against nitric oxide-mediated cellular damage may be through other signal transduction pathways rather than direct scavenging of nitric oxide.…”
Section: Résultats : La Quantité D'oxyde Nitrique Dans Les Macrophagementioning
confidence: 59%
“…In a human leukocyte chemiluminescence study, Demiryurek et al reported that PPF possesses a direct scavenging effect on hydroxyl chloride, superoxide, hydrogen peroxide and hydroxyl radical. 10 Our data suggest that PPF has no such effects on the direct scavenging of nitric oxide. Therefore, the protective mechanism of PPF against nitric oxide-mediated cellular damage may be through other signal transduction pathways rather than direct scavenging of nitric oxide.…”
Section: Résultats : La Quantité D'oxyde Nitrique Dans Les Macrophagementioning
confidence: 59%
“…Additionally, catecholamines and glucocorticoids, released during anesthesia, impaired the immune system (Elenkov and Chrousos, 2002) because the lymphocyte production and function decreased (Inada et al, 2004). However, we suggested that these factors did not influence white blood cell counts because propofol provides an enhancement in antioxidant efficacies (Murphy et al, 1992;Demiryurek et al, 1998) and promotes lower release of catecholamines (Elenkov and Chrousos, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Ko et al has reported that propofol has a preventive effect on ventricles after a global ischemia of the heart [18]. And other similar models of I/R injury on neurons [19], leucocytes [4] and erythrocytes [20] prooved that propofol has a preventive effect against I/R injury. Aarts et al has reported that propofol has a preventive role in cases such as coronary artery transplantation surgery, sepsis and burns, which of all lead into a decreased ontioxidising defense mechanism [13].…”
Section: Discussionmentioning
confidence: 95%
“…Chemical structure of propofol (2,6-diisoproyl phenol) mimics butilised hydroxy toluen (BHT) and endogenous antioxidising agent alpha-tocopherol (vitamin E) which are phenol containing free oxygen radical scavengers and contains a phenolic hydroxy group [13]. All these molecules form complexes with either the cellular membranes or its structural components resulting in a less reactive molecules and each single propofol molecule can scavenger two free oxygen radicals [3,4]. Its also reported that propofol functions as both peroxynitrite scavenger which is produced by superoxide radicals binding to nitric oxide physiologically and inhibiting lipid peroxidation on cellular membranes [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation